Quaid e azam quize - Zohrab, babar (Rumail house of publication Karachi, 2016)
"Quaid-e-Azam Muhammad Ali Jinnah" is a biographical account of the visionary leader who played a pivotal role in the creation of Pakistan, highlighting his determination, leadership, and unwavering commitment to the rights and independence of the Muslim community.